OP0018 Hyperuricemia Increases Mortality Only in Patients with Gout and Existing Cardiovascular Disease. A Prospective Analysis from The Busselton Health Study. (15th July 2016) - Nossent, J.; Raymond, W.; Divitini, M.; Host, L.; Knuiman, M.
Abstract : Background: Hyperuricemia is increasingly prevalent and associated with cardiovascular disease [1]. While hyperuricemia can induce endothelial dysfunction, oxidative stress and inflammation uncertainty remains regarding the association between hyperuricemia and vascular events [2, 3]. Objectives: Investigate whether baseline and/or time averaged UA levels were associated with cardiovascular events and mortality in the Busselton Health Study (BHS) cohort. Methods: Prospective study of the BHS cohort (n=4, 171), using baseline serum UA measures and 15 year follow-up [4]. Outcomes included were cardiovascular events (CVE) and mortality, derived from State-wide registries. Hazard ratios (HR) for UA level as continuous and categorical (low, medium, high) predictor of outcomes, stratified for baseline cardiovascular disease and a history of gout were analysed by multivariate Cox regression. Results: Hyperuricemia was present in 9.4% in participants free of CVE and 16.5% in those with CVE at baseline. In those free of CVE (n=3, 475), a 0.1mmol/L rise in UA level was associated with increased mortality (HR 1.19, CI 1.04–1.36), cardiovascular mortality (HR 1.27, CI 1.03–1.57) and first CVE (HR 1.28, CI 1.13–1.44) after age & sex adjustment. Hyperuricemia significantly increased the risk of a first CVE (HR 1.52, CI 1.13–2.04). However, adjustment for a range of traditional cardiovascular risk factors attenuated these associations. Results were similar for the subset of 2, 139 participants using multiple UA measures over time. In the fully adjusted model, gout was a significant independent predictor of mortality only in participants with a history of CVE at baseline (HR 1.75; CI 1.04–2.95). Conclusions: Hyperuricemia is highly prevalent in the Busselton region of Western Australia and independently increased the risk CVE or mortality events in those with existing CVE and gout. UA lowering therapy for CVE prevention is advisable for patients with a history of gout and CVE, but clearly not warranted in those with asymptomatic hyperuricemia. References: Robinson, PC., et al., An Observational Study of Gout Prevalence and Quality of Care in a National Australian General Practice Population. Journal of Rheum., 2015 Kanbay, M., et al., The role of uric acid in the pathogenesis of human cardiovascular disease. Heart, 2013 van Durme, C., et al., Cardiovascular Risk Factors and Comorbidities in Patients with Hyperuricemia and/or Gout: A Systematic Review of the Literature. Journal of Rheum., 2014 Knuiman, MW., et al., Utility of the metabolic syndrome and its components in the prediction of incident cardiovascular disease: a prospective cohort study. Eur J Cardiovasc Prev Rehabil, 2009 Disclosure of Interest: None declared